The present moment and Caribbean future : the challenges and prospects : draft - Anthony, Kenny ([s.n.] [S.l.], 2008)
Focuses on some of the problems confronting the Caricom Single Market and Economy. Offers some suggestions to restore credibility to the process of reinvigorating the CSME.